Community Participation in Domestic Waste Management in Vim Village Abepura District Jayapura City - Lazarus Ramandei (Diponegoro University, 2022)
Household waste production is increasing every day as the number of products and consumption patterns increases. To overcome the waste volume increase can be done by: reducing the volume of waste from the source through community empowerment. The research on community-based waste management in Vim Village Abepura District Jayapura City aims to: (1) obtain an overview of community-based waste management planning and process, (2) to inventory challenges and opportunities in domestic waste management, (3) community-based waste management. The type of this research is descriptive qualitative, that is research which intends to describe phenomenon that happened at research location. Data collection techniques include interviews, questionnaires, observations and documentation, while the data analysis uses qualitative descriptive techniques. The result of this research concludes that domestic waste management in Vim Village Jayapura City can reduce waste disposal to TPA, but not optimally implemented either in sorting and or in composting because of limited facilities and infrastructure. The composition of waste generation in Vim Village Jayapura City consists of: organic garbage 50.75%, plastic 17.14%, 19.42% paper, glass/metal 12.70%. Organic waste utilized to compost will reduce waste generation and reduce environmental burden, while sorting result not only can reduce waste generation but also can be sold or managed so as to increase revenue. Suggestions based on the results of the research can be given as follows: (1) Government needs to do more socialization about waste management. (2) Waste management is done with 3R principles (reduce, reuse, recycle).